Sodium niobate-based energy storage ceramic material and preparation method thereof
By introducing Sr0.7Bi0.2Mg1/3Nb2/3O3 and BaTiO3 into sodium niobate-based ceramic materials, and using solid-phase reaction method to sinter, the problems of insufficient breakdown field strength and energy storage density of existing ceramic materials were solved, and high Ceramic materials with breakdown strength and high energy storage density.
Patent Information
- Application Number
- CN202411608490.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
It is difficult to make major breakthroughs in the breakdown field strength and energy storage density of existing sodium niobate-based energy storage ceramic materials, and the phase transition between the antiferroelectric P phase and the metastable ferroelectric Q phase leads to poor energy storage performance.
By introducing Sr0.7Bi0.2Mg1/3Nb2/3O3 substrate material and BaTiO3 material, the solid phase reaction method is sintered to make sodium niobate-based energy storage ceramic material, so as to achieve the coexistence of relaxation phase and the electrical phase, thereby improving the breakdown strength and polarity Strength.
The high breakdown strength of ceramic materials (not less than 1140kV/cm) and high energy storage density (not less than 25.86J/cm3) are achieved, while reducing polarization hysteresis and improving the overall performance of the material.
Smart Images

Figure CN119430927A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic material preparation, and in particular to a sodium niobate-based energy storage ceramic material and a preparation method thereof. Background Art
[0002] Dielectric capacitors have a relatively high power density (about 10 8 W / kg), ultra-fast charge and discharge speed (in microseconds or nanoseconds), and low cost make it an ideal material for pulse power systems. However, compared with other energy storage devices, the low energy storage density of dielectric capacitors limits their development towards miniaturization and lightweight of electronic components, and cannot meet the needs of practical applications. Therefore, the study of dielectric capacitors with high energy storage density has attracted much attention and has become a current research hotspot.
[0003] Sodium niobate (NaNbO3, NN for short) is an environmentally friendly energy storage ceramic material. With its unique wide band gap (greater than 3.25 eV) and high polarization strength (reaching 38 μC / cm at 125 kV / cm), it can 2 ) provide the necessary conditions for dielectric energy storage. However, due to the similar free energy between the antiferroelectric P phase and the metastable ferroelectric Q phase in NaNbO3, an irreversible phase transition from the antiferroelectric P phase to the ferroelectric Q phase occurs under an applied electric field or increased temperature, resulting in poor energy storage performance and a square hysteresis loop.
[0004] In order to improve the energy storage performance of NN ceramics, it is generally necessary to optimize the preparation process, chemically modify, introduce other perovskite oxides with low tolerance factors to form a solid solution stable antiferroelectric phase, or introduce cations with different ionic radii and valence states to break the long-range ferroelectric domains and form short-range nanodomains to enhance relaxation performance and reduce polarization hysteresis. For example, the preparation process can be improved by improving the sintering method or using a rolling process; in terms of chemical modification, perovskite oxides with low tolerance factors such as calcium zirconate (CaZrO3) and strontium zirconate (SrZrO3) can be introduced, or bismuth ions (Bi 3+ ), iron ions (Fe 3+ ), niobium ions (Nb 5 + ), magnesium ion (Mg 2+ ) and other cations. Studies have shown that the introduction of Bi, Sr, and Mg elements enhances the relaxation and insulation properties of NN-based ceramics to a certain extent, effectively reduces the polarization intensity, and improves the energy storage efficiency. However, its maximum polarization intensity is too low, which limits the further improvement of energy storage density.
[0005] In addition, it is difficult to achieve a major breakthrough in the breakdown field strength and energy storage density of existing NN-based energy storage ceramics, that is, the breakdown field strength is lower than 1000kV / cm, and the energy storage density is lower than 20J / cm. 3 . Generally speaking, although the ferroelectric Q phase in NN can improve the polarization strength, it will in turn deteriorate the dielectric breakdown strength; while a high content of paraelectric phase is beneficial to improve the dielectric breakdown strength, it will reduce the polarization strength of dielectric ceramics. Therefore, it is urgent to develop a new type of NN-based ceramic material to balance the existence of these two phases and achieve a dual improvement in the high breakdown strength and high energy storage performance of NN-based ceramics. Summary of the invention
[0006] In view of this, the present invention proposes a sodium niobate-based energy storage ceramic material with ultra-high breakdown strength and energy storage density and a preparation method thereof.
[0007] In one aspect, the present invention provides a sodium niobate-based energy storage ceramic material, the general chemical formula of which is:
[0008] (1-x)(0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3)-xBaTiO3 (Ⅰ);
[0009] In formula (I), x is a molar fraction, and its value range is 0.05≤x≤0.20.
[0010] Based on the above technical solution, preferably, the value of x is one of 0.05, 0.10, 0.15 or 0.20.
[0011] By adopting the above technical solution and adjusting the value of x within a suitable range, the material properties can be optimized, thereby improving the energy storage density, dielectric breakdown strength and dielectric properties, and meeting the requirements of high energy storage density and high breakdown strength.
[0012] Furthermore, the breakdown field strength of the ceramic material is not less than 1140 kV / cm, and the total energy storage density is not less than 25.86 J / cm 2 .
[0013] By adopting the above technical solution, it is shown that the ceramic material of the present invention can not only store more energy per unit volume, but also work safely at higher voltages and will not easily break down, thereby ensuring the reliability of the system and providing favorable guarantees for the long-term operation of the system, making the material have great application potential in the field of high-performance electronic devices.
[0014] On the other hand, the present invention provides a method for preparing the sodium niobate-based energy storage ceramic material, wherein the ceramic material is composed of NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The O3 base material and the BaTiO3 material are sintered by a solid phase reaction method.
[0015] By adopting the above technical solution, Sr is introduced into NaNbO3 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3, the coexistence of the relaxation phase and the paraelectric phase (weak polar phase) is achieved, which makes the ceramic have the advantages of high breakdown strength and low polarization hysteresis. On this basis, the further introduction of BaTiO3 with high polarization strength can improve the polarization strength of NN-SBMN ceramics. 2+ The larger ion radius increases the lattice strain energy of the ceramic matrix, inhibits grain boundary migration, and prevents grain growth, thereby further improving the breakdown strength to achieve high-performance sodium niobate-based energy storage ceramic materials with both high breakdown strength and high energy storage density.
[0016] At the same time, the solid phase method is relatively simple to operate and usually does not require complex equipment or reaction conditions. At the same time, a more uniform reaction precursor can be obtained, which helps to obtain a uniform final product. Other sintering methods are more expensive. For example, gas phase sintering can better ensure the purity of the material but requires special equipment and a vacuum environment. Although cold sintering reduces the complex steps in the sintering process and improves production efficiency, it requires special equipment, which increases costs.
[0017] The method specifically comprises the following steps:
[0018] S1, determine the stoichiometric ratio according to the chemical formula, prepare the raw materials according to the stoichiometric ratio, and prepare NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 base material;
[0019] S2, the NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 After the O3 substrate material and the BaTiO3 material are mixed with the solvent, ball milling is performed once;
[0020] S3, drying step S2 after the solution is ball-milled once, grinding to obtain powder;
[0021] S4, pre-sintering the powder in step S3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature;
[0022] S5, grinding the powder of step S4, mixing with a solvent, and performing secondary ball milling;
[0023] S6, drying the solution after the second ball milling in step S5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles;
[0024] S7, pressing the powdered particles from step S6 into tablets to obtain round green pieces;
[0025] S8, sintering the round green body of step S7 into porcelain, cooling it naturally after lowering the temperature, and grinding it thin to obtain a ceramic material.
[0026] By adopting the above technical scheme, sodium niobate-based energy storage ceramic materials with precise chemical composition, uniform particle size, high density and good crystal phase stability can be prepared. These measures not only ensure that the final material has high breakdown strength, high energy storage density and low polarization hysteresis, but also can be used in the fields of high-performance electronic devices, such as high-frequency electronic equipment, pulse power systems, etc.
[0027] Furthermore, the NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The preparation of O3 substrate materials adopts the following steps:
[0028] A1. Prepare raw materials according to stoichiometric ratio, wherein the raw materials include Na2CO3, Nb2O5, Bi2O3, SrCO3 and MgO;
[0029] A2, mixing the raw materials of step A1 with a solvent, and then performing a ball milling;
[0030] A3, Drying Step A2 After the solution is ball-milled once, grind it to obtain a powder;
[0031] A4, pre-sintering the powder in step A3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature;
[0032] A5, grinding the powder of step A4, mixing with solvent, and performing secondary ball milling;
[0033] A6. Drying the solution obtained by the second ball milling in step A5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles;
[0034] A7, pressing the powdered particles from step A6 into tablets to obtain round green pieces;
[0035] A8, sinter the round green body of step A7 into porcelain, cool it down and then naturally cool it, grind it thinly, and obtain NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 base material.
[0036] By adopting the above technical solution, due to the similar free energy between the antiferroelectric P phase and the metastable ferroelectric Q phase in NaNbO3, an irreversible phase transition from the antiferroelectric P phase to the ferroelectric Q phase will occur under the action of an external electric field or elevated temperature, resulting in a large polarization hysteresis and a square hysteresis loop, resulting in poor energy storage performance. 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 After O3, the coexistence of the relaxation phase and the paraelectric phase (weakly polar phase) can be achieved, thereby enabling the base material to exert the advantages of high breakdown strength and low polarization hysteresis, and ultimately achieving higher energy storage efficiency and energy storage density.
[0037] Furthermore, the ball milling time is 8 hours, and the rotation speed is 350 r / min; the prerequisites for the ball milling are: the total mass of the ball milling beads is 284 g; the diameters of the ball milling beads are 10 mm, 8 mm and 5 mm, and the ratio of the ball milling beads with corresponding diameters is 2:3:5; the total volume of the ball milling beads and the mixed liquid is 1 / 2 of the ball milling device.
[0038] By adopting the above technical solution, if the ball milling time is too long, the surface zirconium powder of the ball milling beads will fall off and mix into the solution, while if the ball milling time is too short, the degree of material refinement will be affected; appropriately increasing the rotation speed can increase the kinetic energy of the grinding medium, thereby enhancing the collision and friction between particles and improving the grinding efficiency; the number and weight of the ball milling beads also directly affect the grinding effect, and the appropriate ratio can ensure that the ball milling beads move fully in the tank, increase collision and friction, and thus improve the degree of material refinement. By adopting the above technical solution, the ball milling time, rotation speed and the ratio of the ball milling beads can be reasonably controlled, which can effectively avoid the contamination of zirconium powder, while ensuring the full refinement of the material and improving the grinding efficiency.
[0039] On the basis of the above technical solution, preferably, the ball milling beads are zirconium balls.
[0040] First, a longer ball milling time ensures sufficient mixing of the raw materials, helps reduce the difference in particle size, and improves the uniformity of the final material; a moderate rotation speed can both ensure the efficiency of the ball milling and avoid heat accumulation caused by excessively high rotation speed, which affects the quality of the material and increases energy consumption.
[0041] Secondly, a reasonable total mass of ball mill beads can ensure sufficient impact and grinding force, which helps to improve the refinement of the mixed liquid. The effective cooperation of ball mill beads of different sizes not only ensures the effective crushing of large particles, but also avoids excessive grinding of fine particles.
[0042] Finally, the proper filling amount can ensure that the ball milling beads move more freely within the ball mill, thereby improving the grinding efficiency.
[0043] By adopting the above technical solution, a more efficient and precise ball milling process can be achieved, laying the foundation for the subsequent preparation of uniform, fine and well-dispersed powder. In addition, this process also helps to improve the uniformity, density and performance of the final sodium niobate-based energy storage ceramic material, ensuring its excellent performance in practical applications.
[0044] Furthermore, in step S4, the pre-sintering temperature is 850°C; the holding time is 3h; the cooling rate is 5°C / min, and the temperature drops to 450°C.
[0045] By adopting the above technical solution, the initial reaction between powders can be promoted to form a stable crystal phase, and some impurities can be removed to improve the purity and stability of the material.
[0046] Furthermore, the concentration of the polyvinyl alcohol solution is 3 wt %.
[0047] By adopting the above technical solution, the powder can be effectively bonded together to ensure that every part of the powder can be wrapped by the PVA solution, so as to form uniform particles during the granulation process while maintaining good fluidity. In addition, the 3wt% polyvinyl alcohol solution helps to form particles with good fluidity and compressibility, which is beneficial for subsequent tableting. It can improve the stability of molding and reduce cracks and defects during the molding process. It will not leave obvious residues after decomposition at high temperature, which helps the uniform sintering of ceramic materials and reduces pores and other defects.
[0048] Furthermore, in step S7, the tableting pressure is 20 MPa; the round green body is also required to be maintained at a pressure of 200 MPa for 5 minutes.
[0049] By adopting the above technical solutions, the green body density and molding stability can be improved, while defects can be reduced, its electrical properties can be optimized, and further cold isostatic pressing can be facilitated. Holding the pressure at a higher pressure can help squeeze out pores and improve density, which is the key to ensuring good dielectric properties. A 5-minute holding time can enhance the tightness of contact between particles, reduce internal defects, and improve the uniformity and consistency of the material.
[0050] Further, in step S8, the round green body of step S7 is sintered into porcelain, cooled and then naturally cooled to obtain a ceramic material, which specifically includes:
[0051] The round green body of step S7 is heated to 600°C at 2°C / min and kept at that temperature for 6 hours, then heated to the sintering temperature at 5°C / min and kept at that temperature for 3 hours, then cooled to 450°C at 5°C / min, naturally cooled, and ground to obtain a ceramic material; the sintering temperature is 1170-1220°C.
[0052] By adopting the above technical solution, the gradual heating and cooling method helps to reduce the thermal stress inside the material, avoid the generation of cracks and defects, and thus improve the density and uniformity of the material. In addition, the appropriate holding time ensures the full progress of the chemical reaction, optimizes the microstructure of the material, improves the mechanical strength and electrical properties of the final ceramic material, and ensures its excellent performance in practical applications.
[0053] Furthermore, the thickness of the ceramic material is 50-60 μm.
[0054] By adopting the above technical solutions, the energy storage density and dielectric properties of the material can be significantly improved. This thin layer design not only helps to improve the breakdown strength of the material and reduce internal defects, but also optimizes its performance in high-frequency applications, making it exhibit excellent performance in applications such as pulse power systems that require high energy output and fast charging and discharging, while achieving miniaturization and lightweighting of electronic components.
[0055] The sodium niobate-based energy storage ceramic material provided by the present invention has the following beneficial effects compared with the prior art:
[0056] 1. The preparation method of the NN-based ceramic material prepared by the present invention has simple process, readily available raw materials, high production efficiency, and is suitable for large-scale practical production applications.
[0057] 2. (1-x)(0.6NaNbO3-0.4Sr prepared by the present invention 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3)-xBaTiO3 ceramic material not only has high polarization strength and high breakdown strength, but also has extremely high energy storage density. This ceramic material is a lead-free, environmentally friendly, excellent energy storage ceramic, and its performance is significantly better than other system ceramics, which can meet the requirements of its application in pulse dielectric capacitors and other aspects.
[0058] 3. When preparing sodium niobate-based ceramic materials, the present invention adopts a step-by-step heating and cooling sintering method, which avoids phase changes that may be induced by too fast heating and cooling and grain size growth caused by too slow cooling, thereby improving the phase stability and energy storage performance of the ceramic.
[0059] 4. The present invention uses 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 ceramic material is used as the matrix, and the energy storage performance of the matrix is regulated by doping ferroelectric material BaTiO3. BaTiO3 is used to modify 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 energy storage ceramic material, with the increase of doping amount, improves its polarization strength and breakdown strength, so as to achieve two aspects of energy storage advantages:
[0060] (1) Further improve the polarization strength of ceramics;
[0061] (2) The breakdown strength is further improved.
[0062] 5. The ceramic material prepared by the present invention has a breakdown field strength of not less than 1140 kV / cm and an energy storage density of not less than 25.86 J / cm 2 , the performance is significantly better than other system ceramic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0064] Figure 1 This is the XRD pattern of the sodium niobate-based energy storage ceramic material prepared in Example 1 of the present invention;
[0065] Figure 2 This is a breakdown field strength diagram of the sodium niobate-based energy storage ceramic material prepared in Example 1 of the present invention;
[0066] Figure 3 This is an electron microscope image of the sodium niobate-based energy storage ceramic sample prepared in Example 1 of the present invention. In the figure, a is 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 ceramic sample, b is the ceramic sample prepared in Example 1;
[0067] Figure 4The ultraviolet-visible absorption spectrum diagram and its local magnified diagram of the sodium niobate-based energy storage ceramic sample prepared in Example 1 of the present invention; in the figure, a is the absorption spectrum diagram; b is the ultraviolet-visible absorption spectrum diagram, and c is the local magnified diagram of the ultraviolet-visible absorption spectrum diagram;
[0068] Figure 5 The hysteresis loop of the sodium niobate-based energy storage ceramic prepared in Example 1 of the present invention under the breakdown electric field;
[0069] Figure 6 This is a relationship diagram of the effective energy storage density and energy storage efficiency of the sodium niobate-based energy storage ceramic prepared in Example 1 of the present invention versus the electric field intensity. DETAILED DESCRIPTION
[0070] Xie et al. (DOI:10.1016 / j.jmat.2021.11.012) doped (Bi 0.5 K 0.5 )ZrO3 induces relaxation phase transition and improves relaxation performance to increase the effective energy storage density. Although the ceramic has a high 2 The polarization strength of the ceramic is less than 450 kV / cm, but the polarization characteristics of relaxor ferroelectrics usually show obvious hysteresis. Under high electric fields, the energy loss in the polarization and depolarization process may cause local heating, thereby reducing the overall breakdown strength of the material, making the breakdown strength of the ceramic less than 450 kV / cm, and the final energy storage density is only 4.4 J / cm 3 Guo et al. (DOI:10.1016 / j.ceramint.2024.09.350) used 0.8 (Na 0.5 Li 0.5 NbO3)-0.2(Sr 0.5 Bi 0.5 )(Fe 0.5 Ti 0.25 Zr 0.25 )O3 ceramics by adding MnO, which significantly improved the energy storage performance of high entropy ceramics and achieved 7.93 J / cm 3 The effective energy storage density is 90.6%, but the breakdown strength is only 500kV / cm, which limits the further improvement of its energy storage performance. Zhang et al. (DOI:10.1016 / j.jmat.2021.09.007) introduced (Bi 0.8 Sr 0.2 )(Fe 0.9 Nb 0.1 )O3 is used to construct a relaxor antiferroelectric ceramic, which combines the advantages of antiferroelectric and relaxor ferroelectric, exhibits a stable antiferroelectric phase and enhanced dielectric relaxation behavior, and its breakdown strength reaches 970kV / cm, and finally achieves 16.5J / cm 3Ultra-high effective energy storage density and 83.3% energy storage efficiency.
[0071] In view of the fact that the prior art does not meet the inventor's expectations, the inventor made the present invention through further research.
[0072] The present invention prepares NaNbO3-Sr in advance. 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 substrate material provides ceramic materials with the advantages of high breakdown strength and low polarization hysteresis. On this basis, the substrate material and BaTiO3 material are directly sintered by solid phase sintering method, which further improves the polarization strength of NN-SBMN ceramics. 2+ The larger ion radius increases the lattice strain energy of the ceramic matrix, inhibits grain boundary migration, and prevents grain growth, thereby further improving the breakdown strength to achieve high-performance sodium niobate-based energy storage ceramic materials with both high breakdown strength and high energy storage density.
[0073] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0074] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.
[0075] Table 1 Material source description
[0076]
[0077] The following preparation examples of the present invention, Preparation Examples 1 to 3 respectively provide a base material, and Preparation Example 4 provides a BaTiO3 material.
[0078] Preparation Example 1
[0079] The 0.7NaNbO3-0.3Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The O3 substrate material is prepared by the following steps:
[0080] S1. Prepare raw materials according to stoichiometric ratio, wherein the raw materials include Na2CO3, Nb2O5, Bi2O3, SrCO3 and MgO;
[0081] S2, mixing the raw materials of step S1 with a solvent, and then performing a ball milling;
[0082] S3, drying step S2 after the solution is ball-milled once, grinding to obtain powder;
[0083] S4, pre-sintering the powder in step S3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature;
[0084] S5, grinding the powder of step S4, mixing with a solvent, and performing secondary ball milling;
[0085] S6, drying the solution after the second ball milling in step S5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles;
[0086] Specifically: the polyvinyl alcohol solution has a concentration of 3 wt %, is mixed with the powder into a slurry, and then ground into a powder.
[0087] S7, pressing the powdered particles from step S6 into tablets to obtain round green pieces;
[0088] Specifically: the green body formed by tableting needs to be placed in a cold isostatic press and maintained at a pressure of 200 MPa for 5 minutes.
[0089] S8, sintering the round green body of step S7 into porcelain, cooling it naturally after lowering the temperature, and grinding it thin to obtain a ceramic material.
[0090] Specifically: increase the temperature to 600°C at 2°C / min and keep it for 6 hours, then increase the temperature to 1150°C at 5°C / min and keep it for 3 hours.
[0091] The base material obtained in this preparation example has a dielectric constant of 160 kHz and a breakdown strength of 80 kV / cm.
[0092] Preparation Example 2
[0093] The 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The O3 substrate material is prepared by the following steps:
[0094] S1. Prepare raw materials according to stoichiometric ratio, wherein the raw materials include Na2CO3, Nb2O5, Bi2O3, SrCO3 and MgO;
[0095] S2, mixing the raw materials of step S1 with a solvent, and then performing a ball milling;
[0096] S3, drying step S2 after the solution is ball-milled once, grinding to obtain powder;
[0097] S4, pre-sintering the powder in step S3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature;
[0098] S5, grinding the powder of step S4, mixing with a solvent, and performing secondary ball milling;
[0099] S6, drying the solution after the second ball milling in step S5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles;
[0100] Specifically: the polyvinyl alcohol solution has a concentration of 3 wt %, is mixed with the powder into a slurry, and then ground into a powder.
[0101] S7, pressing the powdered particles from step S6 into tablets to obtain round green pieces;
[0102] Specifically: the green body formed by tableting needs to be placed in a cold isostatic press and maintained at a pressure of 200 MPa for 5 minutes.
[0103] S8, sintering the round green body of step S7 into porcelain, cooling it naturally after lowering the temperature, and grinding it thin to obtain a ceramic material.
[0104] Specifically: increase the temperature to 600°C at 2°C / min and keep it for 6 hours, then increase the temperature to 1150°C at 5°C / min and keep it for 3 hours.
[0105] The base material obtained in this preparation example has a dielectric constant of 200 kHz and a breakdown strength of 120 kV / cm.
[0106] Preparation Example 3
[0107] The 0.5NaNbO3-0.5Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The O3 substrate material is prepared by the following steps:
[0108] S1. Prepare raw materials according to stoichiometric ratio, wherein the raw materials include Na2CO3, Nb2O5, Bi2O3, SrCO3 and MgO;
[0109] S2, mixing the raw materials of step S1 with a solvent, and then performing a ball milling;
[0110] S3, drying step S2 after the solution is ball-milled once, grinding to obtain powder;
[0111] S4, pre-sintering the powder in step S3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature;
[0112] S5, grinding the powder of step S4, mixing with a solvent, and performing secondary ball milling;
[0113] S6, drying the solution after the second ball milling in step S5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles;
[0114] Specifically: the polyvinyl alcohol solution has a concentration of 3 wt %, is mixed with the powder into a slurry, and then ground into a powder.
[0115] S7, pressing the powdered particles from step S6 into tablets to obtain round green pieces;
[0116] Specifically: the green body formed by tableting needs to be placed in a cold isostatic press and maintained at a pressure of 200 MPa for 5 minutes.
[0117] S8, sintering the round green body of step S7 into porcelain, cooling it naturally after lowering the temperature, and grinding it thin to obtain a ceramic material.
[0118] Specifically: increase the temperature to 600°C at 2°C / min and keep it for 6 hours, then increase the temperature to 1150°C at 5°C / min and keep it for 3 hours.
[0119] The base material obtained in this preparation example has a dielectric constant of 180 kHz and a breakdown strength of 110 kV / cm.
[0120] Preparation Example 2 (0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3) Compared with Preparation Example 1 and Preparation Example 3, it shows significant advantages in both dielectric constant and breakdown strength. Specifically, the dielectric constant of Preparation Example 2 reaches 200kHz, which is higher than 160kHz of Preparation Example 1 and 180kHz of Preparation Example 3; at the same time, its breakdown strength is 120kV / cm, which is also significantly better than 80kV / cm of Preparation Example 1 and 110kV / cm of Preparation Example 3. This means that Preparation Example 2 has higher energy storage capacity and stronger high voltage resistance in terms of electrical properties, and is more suitable for application in high-performance electronic components and high-frequency equipment.
[0121] In summary, the inventors prepared 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 Taking O3 substrate material as an example, sodium niobate-based ceramic materials as shown in Examples 1 to 3 were prepared by solid phase sintering with BaTiO3 material having ferroelectricity.
[0122] Example 1
[0123] The general chemical formula of the sodium niobate-based ceramic material of this embodiment is as follows: 0.85(0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg1 / 3 Nb 2 / 3 O3)-0.15BaTiO3, the ceramic material is prepared by the following steps:
[0124] Step S1: Referring to Preparation Example 2, prepare raw materials BaCO3 and TiO2 (molar ratio is 1:1);
[0125] Step S2: placing the powder of step S1 in a nylon ball milling jar containing zirconium balls, mixing with anhydrous ethanol as a solvent, setting the rotation speed of the planetary ball mill device to 350r / min, and ball milling for 8h; wherein: the total mass of the zirconium balls is 284g; the diameters of the zirconium balls are 10mm, 8mm and 5mm, and the proportions of the zirconium balls with corresponding diameters are 2:3:5; the total volume of the zirconium balls and the mixed liquid is 1 / 2 of the ball milling device;
[0126] Step S3: placing the mixed solution obtained after ball milling in step S2 in a drying oven at a temperature of 70° C. for drying, and then fully grinding the dried powder in a mortar for 20 minutes;
[0127] Step S4: the powder ground in step S3 is placed in a crucible, and then placed in a muffle furnace, sintered at 850°C and kept warm for 3 hours, then cooled to 450°C at a rate of 5°C / min and naturally cooled to room temperature;
[0128] Step S5: The powder pre-sintered in step S4 is placed in a mortar and pre-grinded for 20 minutes, then poured into a ball mill equipped with zirconium beads, mixed with anhydrous ethanol as a solvent, and the speed of the ball mill is set to 350 r / min, and the ball milling is performed for 8 hours;
[0129] Step S6: After the mixed solution after ball milling in step S5 is dried in a drying oven at a temperature of 70° C., the polyvinyl alcohol solution is added and mixed, and the mixture is fully ground until it is in a dry powder state, thus completing the granulation;
[0130] Step S7: Take an appropriate amount of the powder granulated in step S6, pour it into a mold and apply a force of 20 MPa on a tablet press to obtain a round green body; then put the round green body into a cold isostatic press and maintain the pressure at a pressure of 200 MPa for 5 minutes;
[0131] Step S8: Use the powder pre-sintered in step S4 (the amount is sufficient to completely cover the green body. The powder is 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3O3, the same below) bury the ceramic green body of corresponding components, and place it in a crucible, put it into a muffle furnace and raise the temperature to 600°C at 2°C / min and keep it for 6h, then raise the temperature to 1180°C at 5°C / min and sinter for 3h, then reduce the temperature to 450°C at 5°C / min and naturally cool to room temperature, grind it to obtain a sodium niobate-based energy storage ceramic material with a thickness of 50μm.
[0132] The sodium niobate-based ceramic material 0.85 (0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3)-0.15BaTiO3 related XRD Figure 1 As shown by Figure 1 It can be seen that the ceramic material of this embodiment presents a pure perovskite structure without obvious secondary phase generation, which indicates that Ba 2+ and Ti 4+ It has successfully diffused into the NaNbO3 lattice and formed a good solid solution.
[0133] Example 2
[0134] The general chemical formula of the sodium niobate-based ceramic material of this embodiment is as follows: 0.95(0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3)-0.05BaTiO3, the ceramic material is prepared by the following steps:
[0135] Step S1: Referring to Preparation Example 2, prepare raw materials BaCO3 and TiO2 (molar ratio is 1:1);
[0136] Step S2: placing the powder of step S1 in a nylon ball milling jar containing zirconium balls, mixing with anhydrous ethanol as a solvent, setting the rotation speed of the planetary ball mill device to 350r / min, and ball milling for 8h; wherein: the total mass of the zirconium balls is 284g; the diameters of the zirconium balls are 10mm, 8mm and 5mm, and the proportions of the zirconium balls with corresponding diameters are 2:3:5; the total volume of the zirconium balls and the mixed liquid is 1 / 2 of the ball milling device;
[0137] Step S3: placing the mixed solution obtained after ball milling in step S2 in a drying oven at a temperature of 70° C. for drying, and then fully grinding the dried powder in a mortar for 20 minutes;
[0138] Step S4: the powder ground in step S3 is placed in a crucible, and then placed in a muffle furnace, sintered at 850°C and kept warm for 3 hours, then cooled to 450°C at a rate of 5°C / min and naturally cooled to room temperature;
[0139] Step S5: The powder pre-sintered in step S4 is placed in a mortar and pre-grinded for 20 minutes, then poured into a ball mill equipped with zirconium beads, mixed with anhydrous ethanol as a solvent, and the speed of the ball mill is set to 350 r / min, and the ball milling is performed for 8 hours;
[0140] Step S6: After the mixed solution after ball milling in step S5 is dried in a drying oven at a temperature of 70° C., the polyvinyl alcohol solution is added and mixed, and the mixture is fully ground until it is in a dry powder state, thus completing the granulation;
[0141] Step S7: Take an appropriate amount of the powder granulated in step S6, pour it into a mold and apply a force of 20 MPa on a tablet press to obtain a round green body; then put the round green body into a cold isostatic press and maintain the pressure at a pressure of 200 MPa for 5 minutes;
[0142] Step S8: Use the pre-fired powder in step S4 to bury the ceramic green body of the corresponding component, and place it in a crucible, put it into a muffle furnace, raise the temperature to 600°C at 5°C / min and keep it warm for 6 hours, then raise the temperature to 1200°C at 8°C / min and sinter for 3 hours, then reduce the temperature to 450°C at 10°C / min, cool it naturally to room temperature, and grind it to obtain a sodium niobate-based energy storage ceramic material with a thickness of 50μm.
[0143] Example 3
[0144] The general chemical formula of the sodium niobate-based ceramic material of this embodiment is as follows: 0.8(0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3)-0.2BaTiO3, the ceramic material is prepared by the following steps:
[0145] Step S1: Referring to Preparation Example 2, prepare raw materials BaCO3 and TiO2 (molar ratio is 1:1);
[0146] Step S2: placing the powder of step S1 in a nylon ball milling jar containing zirconium balls, mixing with anhydrous ethanol as a solvent, setting the rotation speed of the planetary ball mill device to 350r / min, and ball milling for 8h; wherein: the total mass of the zirconium balls is 284g; the diameters of the zirconium balls are 10mm, 8mm and 5mm, and the proportions of the zirconium balls with corresponding diameters are 2:3:5; the total volume of the zirconium balls and the mixed liquid is 1 / 2 of the ball milling device;
[0147] Step S3: placing the mixed solution obtained after ball milling in step S2 in a drying oven at a temperature of 70° C. for drying, and then fully grinding the dried powder in a mortar for 20 minutes;
[0148] Step S4: the powder ground in step S3 is placed in a crucible, and then placed in a muffle furnace, sintered at 850°C and kept warm for 3 hours, then cooled to 450°C at a rate of 5°C / min and naturally cooled to room temperature;
[0149] Step S5: The powder pre-sintered in step S4 is placed in a mortar and pre-grinded for 20 minutes, then poured into a ball mill equipped with zirconium beads, mixed with anhydrous ethanol as a solvent, and the speed of the ball mill is set to 350 r / min, and the ball milling is performed for 8 hours;
[0150] Step S6: After the mixed solution after ball milling in step S5 is dried in a drying oven at a temperature of 70° C., the polyvinyl alcohol solution is added and mixed, and the mixture is fully ground until it is in a dry powder state, thus completing the granulation;
[0151] Step S7: Take an appropriate amount of the powder granulated in step S6, pour it into a mold and apply a force of 20 MPa on a tablet press to obtain a round green body; then put the round green body into a cold isostatic press and maintain the pressure at a pressure of 200 MPa for 5 minutes;
[0152] Step S8: Use the pre-fired powder in step S4 to bury the ceramic green body of the corresponding component, and place it in a crucible, put it into a muffle furnace and raise the temperature to 600°C at 1°C / min and keep it warm for 6 hours, then raise the temperature to 1220°C at 1°C / min and sinter for 3 hours, then reduce the temperature to 450°C at 1°C / min and naturally cool to room temperature, grind it thin, and obtain a sodium niobate-based energy storage ceramic material with a thickness of 60μm.
[0153] In the heating stage, Example 1 adopts a rate of 2°C / min to rise to 600°C and keep it warm for 6 hours, and then rises to 1180°C at a rate of 5°C / min and keeps it warm for 3h. Such a heating rate not only ensures the uniform release of internal stress of the material, but also avoids the change of internal structure of the material caused by too fast heating rate, thereby maintaining the stability of the microstructure of the material. In the cooling stage, the temperature is reduced to 450°C at a rate of 5°C / min. Such a cooling rate can effectively control the growth of grains and prevent the grains from being too coarse, thereby affecting the mechanical properties and electrical properties of the material. In contrast, the heating rate of Example 2 is faster (5°C / min to 600°C), and the final sintering temperature is higher (1200°C), which may cause the material to experience faster grain growth during the sintering process, thereby affecting the microstructure and performance of the material. In addition, the cooling rate of Example 2 is also faster (10°C / min), which may cause large residual stress to be generated inside the material, thereby affecting the mechanical strength and electrical properties of the material. The heating and cooling rates of Example 3 are very slow (both 1°C / min). Although this slow heating and cooling process helps to reduce the stress inside the material, it may also cause the grains to grow too fast because the longer holding time provides more growth opportunities for the grains, which may eventually lead to excessive grain size, thereby reducing the overall performance of the material.
[0154] In summary, the heating and cooling rates adopted in Example 1 are moderate, which not only avoids the phase change and abnormal grain growth that may be caused by rapid heating and cooling, but also ensures the uniform release of the internal stress of the material, so that the prepared sodium niobate-based ceramic material has better phase stability and energy storage performance.
[0155] The inventors took the above-mentioned Example 1 as an example, and conducted three performance tests on the sodium niobate-based ceramic material prepared in Example 1, namely, total energy storage density, effective density and energy storage efficiency. The test results are shown in Table 2 below. The above-mentioned performance test methods are all calculated using the hysteresis loop measured by the ferroelectric analyzer Polyk, and the calculation method is:
[0156]
[0157]
[0158]
[0159] In the above formulas (II) to (IV), W, W rec , η are the total energy storage density, effective energy storage density and energy storage efficiency of dielectric ceramics respectively; E, P max , P rThey represent the external electric field to which the dielectric ceramic is subjected, the maximum polarization intensity under the external electric field, and the residual polarization intensity after the electric field is removed. The relationship between the effective energy storage density and the energy storage efficiency with the electric field intensity is as follows: Figure 5 shown.
[0160] Table 2 Performance test results
[0161]
[0162] Combined with the performance test results in Table 2 Figure 2 It can be seen that the data distribution is relatively concentrated, that is, the breakdown strength of most samples is close to 1140kV / cm.
[0163] Combined with the performance test results in Table 2 Figure 3 It can be seen that: a is 0.6NaNbO3-0.4Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 a is the SEM image of the O3 matrix ceramic, b is the SEM image of the ceramic sample prepared in Example 1, and it can be clearly seen that the grain size in b is smaller. The finer the grains, the more grain boundaries there are, thereby improving the electric field distribution and enhancing the anti-puncture capability.
[0164] Combined with the performance test results in Table 2 Figure 4 It can be seen that: Figure (a) shows the change in absorbance of the material at different wavelengths, revealing that the material has a strong absorption capacity for light in the visible light range, especially in the short wavelength region. Figure (b) uses the Tauc plot method to obtain the optical band gap energy of the material, which is about 3.75eV. This value indicates that the material is a wide bandgap semiconductor and is suitable for optoelectronic applications in the ultraviolet and visible light regions.
[0165] Combined with the performance test results in Table 2 Figure 5 It can be seen that the two curves in the figure clearly show that as the electric field strength increases, the polarization intensity also increases, showing a linear growth trend. This phenomenon shows that the material can effectively produce a polarization effect when subjected to an external electric field, thereby achieving charge separation and accumulation. In addition, the figure also mentions that the material exhibits good nonlinear optical properties in the weak electric field range, which means that a significant polarization enhancement effect can be observed even at a smaller electric field strength.
[0166] Combined with the performance test results in Table 2 Figure 6 It can be seen that: with the increase of electric field intensity, the effective energy storage density gradually increases, while the energy storage efficiency first decreases slightly and then stabilizes. This shows that within a certain range of electric field intensity, the energy storage performance of the material will be improved, but at higher electric field intensity, the energy storage efficiency may be affected. Therefore, reasonable control of the electric field intensity is crucial to optimize the energy storage performance of the material.
[0167] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A sodium niobate-based energy storage ceramic material, characterized in that: The general chemical formula of the ceramic material is: <h2 style=";text-align:left;direction:ltr">(1-x)(0.6NaNbO3-0.4Sr<h2 style=";text-align:left;direction:ltr"> 0.7 <h2 style=";text-align:left;direction:ltr"> Bi<h2 style=";text-align:left;direction:ltr"> 0.2 <h2 style=";text-align:left;direction:ltr"> Mg<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> O3)-xBaTiO3(Ⅰ); In formula (I), x is a molar fraction, and its value range is 0.05≤x≤0.
20.
2. The sodium niobate-based energy storage ceramic material according to claim 1, characterized in that: The breakdown field strength of the ceramic material is not less than 1140 kV / cm, and the total energy storage density is not less than 25.86 J / cm 2 .
3. A method for preparing the sodium niobate-based energy storage ceramic material as claimed in claim 1 or 2, characterized in that: The ceramic material is composed of NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The O3 base material and the BaTiO3 material are sintered by a solid phase reaction method.
4. The method according to claim 3, characterized in that The method comprises the following steps: S1, determine the stoichiometric ratio according to the chemical formula, prepare the raw materials according to the stoichiometric ratio, and prepare NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 base material; S2, the NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 After the O3 substrate material and the BaTiO3 material are mixed with the solvent, ball milling is performed once; S3, drying step S2 after the solution is ball-milled once, grinding to obtain powder; S4, pre-sintering the powder in step S3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature; S5, grinding the powder of step S4, mixing with a solvent, and performing secondary ball milling; S6, drying the solution after the second ball milling in step S5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles; S7, pressing the powdered particles from step S6 into tablets to obtain round green pieces; S8, sintering the round green body of step S7 into porcelain, cooling it naturally after lowering the temperature, and grinding it thin to obtain a ceramic material.
5. The method according to claim 4, characterized in that In step S1, the NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 The preparation of O3 substrate materials adopts the following steps: A1. Prepare raw materials according to stoichiometric ratio, wherein the raw materials include Na2CO3, Nb2O5, Bi2O3, SrCO3 and MgO; A2, mixing the raw materials of step A1 with a solvent, and then performing a ball milling; A3, Drying Step A2 After the solution is ball-milled once, grind it to obtain a powder; A4, pre-sintering the powder in step A3, keeping the temperature, then cooling it down, and then naturally cooling it to room temperature; A5, grinding the powder of step A4, mixing with solvent, and performing secondary ball milling; A6. Drying the solution after the second ball milling in step A5, mixing it with the polyvinyl alcohol solution, and grinding it to obtain powder particles; A7, pressing the powdered particles from step A6 into tablets to obtain round green pieces; A8, sinter the round green body of step A7 into porcelain, cool it down and then naturally cool it, grind it thinly, and obtain NaNbO3-Sr 0.7 Bi 0.2 Mg 1 / 3 Nb 2 / 3 O3 base material.
6. The method according to claim 4, characterized in that The ball milling time is 8 hours and the rotation speed is 350r / min; The prerequisites for the ball milling are: the total mass of the ball milling beads is 284 g; the diameters of the ball milling beads are 10 mm, 8 mm and 5 mm, and the ratio of the ball milling beads with corresponding diameters is 2:3:5; the total volume of the ball milling beads and the mixed liquid is 1 / 2 of the ball milling device.
7. The method according to claim 4, characterized in that In step S4, the pre-sintering temperature is 850°C; the holding time is 3h; the cooling rate is 5°C / min, and the temperature drops to 450°C.
8. The method according to claim 4, characterized in that In step S6, the concentration of the polyvinyl alcohol solution is 3 wt %.
9. The method according to claim 4, characterized in that In step S8, the round green body of step S7 is sintered into porcelain, cooled and then naturally cooled to obtain a ceramic material, which specifically includes: The round green body of step S7 is heated to 600°C at 2°C / min and kept at that temperature for 6 hours, then heated to the sintering temperature at 5°C / min and kept at that temperature for 3 hours, then cooled to 450°C at 5°C / min, naturally cooled, and ground to obtain a ceramic material; The sintering temperature is 1170-1220°C.
10. The method according to claim 9, characterized in that The thickness of the ceramic material is 50-60 μm.
Citation Information
Patent Citations
Wide-temperature-range stable energy-storing medium ceramic and preparation method thereof
CN103922734A
Method for regulating curie temperatures of sodium metaniobateceramics
CN110342933A
Transparent medium energy storage ceramic material as well as preparation method and application thereof
CN115536390A
Piezoelectric ceramic composition and piezoelectric ceramic
JP2007261864A
Lead-free piezoelectric porcelain composition
JP2008156172A